2022
DOI: 10.3390/vaccines10020141
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Titers of Circulating Anti-SARS-CoV-2 Antibodies and Risk of COVID-19 Infection in Healthcare Workers during the Nine Months after Immunization with the BNT162b2 mRNA Vaccine

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has had a tremendous impact on health services; hundreds of thousands of healthcare workers (HCWs) have died from coronavirus disease 2019 (COVID-19). The introduction of the BNT162b2 mRNA vaccine in Italy provided recipients with significant protection against COVID-19 within one to two weeks after the administration of the second of the two recommended doses. While the vaccine induces a robust T cell response, the protective role of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 35 publications
4
35
0
Order By: Relevance
“…Moreover, individuals exposed to SARS_CoV-2 prior to the vaccination cycle showed a booster antibody response already seven days from the first dose, compared to very low titers observed in the naïve HCWs. Regarding the role of sex and age on the antibody titer, we observed significantly higher values in women and/or young HCWs in line with some studies [ 7 , 9 , 17 , 19 , 20 , 24 , 26 , 29 , 33 , 35 , 36 , 39 , 40 , 41 , 42 , 44 , 45 ], and in contrast with others who did not observe any statistically significant association [ 13 , 14 , 47 ]. Concerning the antibody titer kinetics, we observed a ~50% decrease of the antibody titer after seven months from the completion of the round of administering the second dose, mainly in previously-infected and elderly HCWs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, individuals exposed to SARS_CoV-2 prior to the vaccination cycle showed a booster antibody response already seven days from the first dose, compared to very low titers observed in the naïve HCWs. Regarding the role of sex and age on the antibody titer, we observed significantly higher values in women and/or young HCWs in line with some studies [ 7 , 9 , 17 , 19 , 20 , 24 , 26 , 29 , 33 , 35 , 36 , 39 , 40 , 41 , 42 , 44 , 45 ], and in contrast with others who did not observe any statistically significant association [ 13 , 14 , 47 ]. Concerning the antibody titer kinetics, we observed a ~50% decrease of the antibody titer after seven months from the completion of the round of administering the second dose, mainly in previously-infected and elderly HCWs.…”
Section: Discussionsupporting
confidence: 90%
“…A total of 57 studies, including additional papers found through a reference scanning (n = 3) and a Google search (n = 1), were screened for full-text review. Forty-four studies were eventually considered appropriate [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] for this literature review, as detailed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12], to improve vaccination uptake. In the background of waning immunity following COVID-19 [41,42] vaccination and the need to boost doses to combat arising new SARS-CoV-2 variants of concern, there remains a continued role for mandates due to persistent vaccine hesitancy. While vaccine mandates affect an individual's choice (right to refuse vaccination), it is critical to remember that every HCW has an ethical and moral responsibility to do no harm and to place their patient's health goals and interests above their own [43].…”
Section: Strategies For Interventionmentioning
confidence: 99%
“…Among the first category is Housset et al (2022) who observed a decrease in anti-spike antibody titer of 84.3% between months 1-6 for Pfizer vaccine, whereas (Levine-Tiefenbrun et al, 2022) analyzed the cycle threshold (Ct) values of RdRp gene, that initially increased by 2.7 relative to unvaccinated in the first month after the booster dose, but then decayed to 1.3 in the second month and found to be small in the third to fourth months. Health care workers -considered to be at higher risk-who received the two doses of the Pfizer vaccine developed protective antibodies that were maintained at detectable levels at least for 250 days after the second dose of the vaccine (Coppeta et al, 2022). Other studies that report reduction in humoral response for several vaccines include Berar-Yanay et al (2021); Kolaric et al (2021); Khoury et al (2021); Peled et al; Levin et al (2021) The estimates of VE are in general relative risk measures, some function of attack ratios (Lin et al, 2022) measured usually through a cohort-study or a test-negative design (Fukushima & Hirota, 2017) and thus provide a comparison between relative risk of vaccinated and unvaccinated groups.…”
Section: Introductionmentioning
confidence: 99%